Linguistic Interventions and the Ethics of Conceptual Disruption - Löhrer, Guido (Ethical theory and moral practice, 2022)
Several authors in psychology and philosophy have recently raised the following question: when is it permissible to intentionally change the meaning and use of our words and concepts? I argue that an arguably prior question has received much less attention: Even if there were good moral or epistemic reasons for conceptual or semantic changes, this does not yet justify pushing or lobbying for such changes if they are socially and conceptually disruptive. In this paper, I develop the beginnings of an ethics of conceptual disruption as well as a set of norms of linguistic interventions based on it.